Availability and Accessibility of Information Sources and the Use of Library Services in Engineering Colleges in Tamil Nadu - Nattar, S.; Duraisingam, A.; Alex, D. (Journal of Information and Knowledge, 2015)
Survey of 1209 students belonging to Engineering colleges in Tamilnadu to study the frequency, purpose of visit to the library and the usefulness of engineering science periodicals reveals that 48.54 % of respondents visit library everyday. About 30.77 percent students visit library to borrow books followed by to read journals and magazines (23.66%). It was found that a large number of users read books followed by periodicals. Concludes that emphasis needs to be given for subscribing online periodicals through e-consortia.